PENGEMBANGAN METODE RAPID TEST DALAM PENENTUAN ASH CONTENT DAN CALORIFIC VALUE BATUBARA DI LABORATORIUM PT JASA MUTU MINERAL INDONESIA - Kumalasari, Anisa; Panggabean, Aman Sentosa; Akkas, Erwin (JURNAL ATOMIK, 2017)
A research on development of rapid test methods for two parameters, calorific value and ash content, based on the needs of minimum time analysis has been conducted. This study aims to determine whether the analytical performance of rapid test methods is comparable with the standard methods. The results showed that the standard and the rapid test method have good analytical performance. Accuracy results which is expressed as recovery percentage show that the calorific values of both methods were in the range of 99.75 % - 100.40 % and the ash content values ​​with both methods were in the range of 93.33 % - 103.70 %. Precision results by CV percentage showed that the calorific value were 0.21 % and 0.23 %, and the value of ash content were 4.03% and 4.28%. For the ruggedness parameter test, the success rate was almost for the entire parameter, excepts for precision test where the ash content value obtained has CV percentage ≥ 5 %. Nevertheless, the overall parameters of the test and the analytical performance analysis are extremely good and acceptable according to the references and a rapid test method can be used as an alternative method.